Cognitive Profiles of Mexican Elementary Education Teachers on School Inclusion of Students with Disability - Ontiveros, Patricia Bustos; Castro-Campos, Claudia; Morales-Martinez, Guadalupe Elizabeth (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
This research investigated the attitudes of 99 elementary education teachers toward the inclusion of students with disabilities in schools. The present authors designed a factorial experiment with 2 (View on learning difficulties: static vs. interactionist) x 2 (Teacher approach: teaching vs. learning) x 2 (Social climate: homogeneous vs. heterogeneous) x 3 (Institutional culture: individualistic vs. delegation vs. collaborative). The orthogonal combination of these factors resulted in 24 experimental conditions ready to build the 24 experimental scenarios of this study. Each scenario described a hypothetical story about the thinking of teachers who faced a school inclusion situation. The experimental task for the participants was to read each scenario individually and then assess their level of identification with the protagonist. The results indicated two types of teacher profiles among the participants: the pre-inclusive profile, which showed a low level of identification towards the inclusive vision, and the inclusive profile, which presented a moderate level of school inclusiveness. The most relevant factors for making inclusive judgments in both groups were the diversity climate (hp2 = 0.24) and professional culture (hp2 = 0.13). However, the pre-inclusive group showed a greater affinity with school homogeneity and individual work. In contrast, the second group showed greater acceptance of diversity and collaboration in school inclusion. In this article, the present authors discuss the implications of these findings within the classroom.